Banks, power, and political institutions: the divergent priorities of European states towards "too-big-to-fail" banks: The cases of competition in retail banking and the banking structural reform. (March 2020) - Massoc, Elsa
Abstract: This article examines how two dynamics, one global and one domestic, have interacted to shape the politics of banking in Europe. In the aftermath of the 2008 crisis, European governments were subject to renewed structural incentive to promote TBTF banks: in financialized economies, the growth of these banks is perceived as an essential element of a national economy's global competitiveness. Yet, this incentive was subject to enhanced political contention at home. Factions—often led by actors from within the state itself—have opposed governments' impetus to promote TBTF banks. The specific identity, preferences and resources of these factions are determined by distinctive political institutions and vary across countries. Through the comparative analysis of banking structural reform and banking competition policies in the UK, France and Germany, I argue that varieties of regulatory outcomes are explained by the differentiated institutional capacity of "anti-TBTF" factions to carry weight in policymaking processes across jurisdictions.